The scope of practice of UK oral surgeons. (May 2015) - Brotherton, P.; Gerrard, G.; Bennett, K.; Coulthard, P.
Abstract: Aim: To investigate the current scope of clinical practice and involvement in postgraduate education and training of UK oral surgeons. Materials and methods: Electronic survey via 'Survey Monkey ™' of members of British Association of Oral Surgeons. Results: Response rate of 39% (208) with margin of error 5.29% at 95% level of confidence. Fifty‐nine per cent (122) regularly operated under general anaesthesia; 39% (47) regularly undertook trauma surgery. A wide range of conditions (including mucosal) were managed and surgical procedures undertaken for paediatric and adult patients. Conclusions: UK oral surgeons are currently undertaking a wide range of procedures as described by the General Dental Council, the Career Development Framework for Consultant Appointments and EU directives and well beyond the limits of minor oral surgery. They also make a significant contribution to education and training in the UK.